1993
DOI: 10.1115/1.2919255
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of the Design Process

Abstract: In concurrent engineering, an attempt is made to perform design and other related activities simultaneously rather than in series as in the case of traditional design. This may result in a reduction of the duration of the design project, cost savings, and better quality of the final design. However, the concurrent engineering approach might increase the complexity of the design process and make it more difficult to manage. One way to reduce the complexity of a large scale design project is to apply decompositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(90 citation statements)
references
References 4 publications
0
87
0
3
Order By: Relevance
“…Kusiak and Wang showed that after an FDT is used to determine appropriate subproblems, the precedence matrix (a form of the DSM) can be used to identify efficient subproblem sequences [14]. Meier et al stated that after sequencing is performed subproblems may be more readily identified [21].…”
Section: Partitioning and Coordination Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Kusiak and Wang showed that after an FDT is used to determine appropriate subproblems, the precedence matrix (a form of the DSM) can be used to identify efficient subproblem sequences [14]. Meier et al stated that after sequencing is performed subproblems may be more readily identified [21].…”
Section: Partitioning and Coordination Decision-makingmentioning
confidence: 99%
“…Formal partitioning approaches using FDT or DSM information are important, as they may identify nonintuitive but useful partitions [14].…”
Section: Partitioning and Coordination Decision-makingmentioning
confidence: 99%
“…These are extensions to the DSM which allow modelling of linkages between different types of element (Kusiak and Wang 1993a;Danilovic and Browning 2007;Lindemann et al 2009;Bartolomei et al 2012). Danilovic and Browning (2007) discuss application of DMMs to explore connectivity between the process domains of tasks, components, and teams.…”
Section: Domain-integrating Task Network Modelsmentioning
confidence: 99%
“…Several DSM-based optimization methods are proposed to reorder the discipline sequence [39,[42][43][44]. These methods try to minimize the number of feedback coupling loops [45,46], or minimize an integrated objective taking other factors, for example, time, cost, and modularity, into account [43,47]. Partitioning a coupled system into several small subsystems is another objective to reduce the complexity of the problems [41,44].…”
Section: The Optimal Discipline Sequence Modelmentioning
confidence: 99%